The contemporary Ukrainian-Russian cross-border cooperation challenges: the spiritual causes and ways of overcoming - Chernomaz, P.A. (INTERREGIONAL OUTREACH NON-GOVERNMENTAL ORGANIZATION “ASSOCIATION OF ORTHODOX SCIENTISTS”, 2015)
Identified the root causes of aggravation of Ukrainian-Russian relations in the light of the spiritual crisis in society.
Keywords: spiritual crisis; Ukrainian-Russian relations; cross-border cooperation